Eosinophilic colitis. (8th March 2016) - Dionísio de Sousa, Isabel José; Bonito, Nuno; Pais, Ana; Gervásio, Helena
Abstract : A 57-year-old man, diagnosed with colon cancer stage III in July/2010, underwent surgery and received adjuvant chemotherapy with FOLFOX 4 (5-fluorouracil; calcium folinate and oxaliplatin), which ended in March/2011 after 12-cycles. It was then decided to maintain periodical surveillance. About 1 year later, the patient developed several episodes of diarrhoea, mainly during the night, and presented persistent peripheral eosinophilia in the blood count (range 585–1300 eosinophils/µL). Colonoscopy was performed, with the histological result showing eosinophilic infiltration of the colon, compatible with eosinophilic colitis. The patient was treated with a short course of budesonide, achieving resolution of symptoms, and has remained asymptomatic.